2020
DOI: 10.1038/s41467-020-18954-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting oxidative phosphorylation to promote the stem and immunoevasive properties of pancreatic cancer stem cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC), the fourth leading cause of cancer death, has a 5-year survival rate of approximately 7–9%. The ineffectiveness of anti-PDAC therapies is believed to be due to the existence of a subpopulation of tumor cells known as cancer stem cells (CSCs), which are functionally plastic, and have exclusive tumorigenic, chemoresistant and metastatic capacities. Herein, we describe a 2D in vitro system for long-term enrichment of pancreatic CSCs that is amenable to biological and CSC-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 54 publications
0
78
0
Order By: Relevance
“…Differentially expressed genes of LINC01133 marked Cluster 0 were also input into IPA and the top Ingenuity Canonical Pathways and Upstream Regulators were also presented. Top pathways, including Oxidative Phosphorylation, EIF2 Signaling and Mitochondrial Dysfunction, were closely associated with stem and immunoevasive properties ( 33 ), tumor biology ( 42 ) and cancer metabolic phenotypes ( 43 ) of pancreatic cancer. Taken together, these ingenuity canonical pathways and upstream regulator analysis consistently confirmed our observation in scRNA-seq data and further identified the MEG + metastatic cancer cell cluster as the leader of cancer cell EMT and metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentially expressed genes of LINC01133 marked Cluster 0 were also input into IPA and the top Ingenuity Canonical Pathways and Upstream Regulators were also presented. Top pathways, including Oxidative Phosphorylation, EIF2 Signaling and Mitochondrial Dysfunction, were closely associated with stem and immunoevasive properties ( 33 ), tumor biology ( 42 ) and cancer metabolic phenotypes ( 43 ) of pancreatic cancer. Taken together, these ingenuity canonical pathways and upstream regulator analysis consistently confirmed our observation in scRNA-seq data and further identified the MEG + metastatic cancer cell cluster as the leader of cancer cell EMT and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…FIGURE 6 | Elevated MEG3 transcript in cancer cells of PDAC mouse models(33). Transcript levels of MEG3 in normal epithelial cells and PDAC cancer cells of mouse models were visualized by split violin plots (A) and UMAPs (B).…”
mentioning
confidence: 99%
“…As the fourth most leading cause of cancer-related death in the world, pancreatic cancer (PC) is usually diagnosed at an advanced stage [ 1 ]. The rising mortality rates from PC has projected it will become the second common cause of tumor-related mortality by the year 2030 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism suggests that metabolic interactions between CSCs and their niche cells are important, especially for the maintenance of CSC mitochondrial OXPHOS. Consistently, a recent study revealed that pancreatic cancer cells are forced to utilize mitochondrial OXPHOS, increase expression of CSC biomarkers and pluripotency genes, and upregulate immune evasion properties through the accumulation of protumor immune cells [ 47 ]. Given these findings, it is possible that elucidation of the relationship between CSCs and their stromal niche will lead to the development of more effective therapies targeting CSC-specific metabolism in combination with conventional therapies, including immunotherapy.…”
Section: Mitochondrial Oxphos Metabolism In Cscsmentioning
confidence: 87%